Γ-Tocotrienol-induced autophagy in malignant mammary cancer cells. (January 2014) - Tiwari, Roshan V; Parajuli, Parash; Sylvester, Paul W
Γ-Tocotrienol, a member of the vitamin E family of compounds, displays potent antiproliferative and cytotoxic effects in a variety of cancer cell types at treatment doses that have little or no effect on normal cell viability or growth. Autophagy is a tightly regulated lysosomal self-digested process that can either promote cell survival or programmed cell death, but the role of autophagy in mediating γ-tocotrienol-induced cytotoxicity in breast cancer is not presently completely understood. Mouse (+SA) and human (MCF-7 and MDA-MD-231) mammary tumor cells lines were exposed to 0–40 µmol/L γ-tocotrienol for a 24 h treatment period. γ-Tocotrienol treatment caused a relatively large increase in the accumulation of monodansylcadaverine (MDC)-labeled vacuoles, a marker of autophagosome formation, in all tumor cell lines. Results also showed that γ-tocotrienol treatment induced an increased conversion of microtubule-associated protein, 1A/1B-light chain 3, from its cytosolic form (LC3B-I) to its lipidated form (LC3B-II), increased Beclin-1 levels, and increased acridine orange staining as determined by flow cytometry analysis, providing further evidence of γ-tocotrienol-induced autophagy in these mammary cancer cell lines. In contrast, similar treatment with γ-tocotrienol was not found to increase autophagy marker expression in immortalized mouse (CL-S1) and human (MCF-10 A) normal mammary epithelial cell lines. Treatment with γ-tocotrienol also caused a reduction in PI3K/Akt/mTOR signaling and a corresponding increase in the Bax/Bcl-2 ratio, cleaved caspase-3, and cleaved poly (ADP-ribose) polymerase (PARP) levels in these cancer cell lines, suggesting that γ-tocotrienol-induced autophagy may be involved in the initiation of apoptosis. In summary, these findings demonstrate that the cytotoxic effects of γ-tocotrienol are associated with the induction of autophagy in a mouse and human mammary cancer cells.